Annual arable land and permanent agriculture extent in Southern Greece from 1986-2020, derived from Landsat and LUCAS data - Aaron M Sparks; Imen Bouhamed; Luigi Bochetti; Ioannis Z Gitas; Chariton Kalaitzidis (PANGAEA, 2022)
This dataset consists of 30 m spatial resolution arable land and permanent agriculture maps for Southern Greece for the period 1986-2020. For this dataset, arable lands are defined as areas where seasonal crops are planted and are typically harvested and tilled at least once a year. Arable land includes cereal crops, root crops, non-permanent industrial crops, dry pulses, vegetables and flowers, and fodder crops. Permanent agriculture is defined as areas with permanent crops including fruit trees, olive groves and vineyards. Mapped regions include Attica, the Peloponnese peninsula, and Crete. Ground observations derived from the European Union statistical office (EUROSTAT) Land Use/Cover Area frame Survey (LUCAS) and Landsat spectral-temporal metrics were used to train a Random Forest classifier, which was used to classify arable land and permanent agriculture at annual time steps. A post-processing step was taken to reduce spurious landcover class transitions using a Hidden Markov Model that accounts for landcover class transition likelihoods and annual class membership likelihoods.